IMPROVING THE LEARNING PROCESS BY USING INTERACTIVE METHODS IN TEACHING ENGLISH (American Journal of Pedagogical and Educational Research, 2023)
This article explores the significance of incorporating interactive methods in teaching English to enhance the learning process. The study delves into various interactive teaching approaches, their impact on student engagement, and the overall effectiveness in language acquisition. The research emphasizes the integration of technology to create a dynamic and participatory learning environment. The article aims to provide insights into the benefits of interactive teaching methods and offers recommendations for educators to implement these strategies in their English language classrooms.